Whole-exome sequencing and bioinformatic analyses revealed differences in gene mutation profiles in papillary thyroid cancer patients with and without benign thyroid goitre background - Eng, Zing Hong; Abdullah, Mardiaty Iryani; Ng, Khoon Leong; Abdul Aziz, Azlina; Arba'ie, Nurul Hannis; Mat Rashid, Nurullainy; Mat Junit, Sarni (Frontiers Media S.A., 2023)
Background: Papillary thyroid cancer (PTC) is the most common thyroid malignancy. Concurrent presence of cytomorphological benign thyroid goitre (BTG) and PTC lesion is often detected. Aberrant protein profiles were previously reported in patients with and without BTG cytomorphological background. This study aimed to evaluate gene mutation profiles to further understand the molecular mechanism underlying BTG, PTC without BTG background and PTC with BTG background.